The Relationship between Compliance with Antihypertensive Drugs and the Life Quality of the Elderly in the Kresnomulyo Village Public Health Center, Pringsewu, Lampung - Hotimah, Etika Khusnul; Wina Safutri; Mida Pratiwi; Diah Kartika Putri (LPPM Universitas Dhyana Pura, 2025)
One major issue in worldwide public health is hypertension. The third-highest rate of hypertension in Ambarawa District is seen in Kresnomulyo Village. In addition to making patients' conditions worse, noncompliance with antihypertensive treatment can result in problems such as heart enlargement, stroke, and kidney failure. Patients' quality of life is affected by their compliance with antihypertensive treatment, which includes both medication and lifestyle changes. The research objective was to analyze the correlation between compliance with antihypertensive medication use and the quality of life of patients at the Kresnomulyo Public Health Center. This research is a non-experimental quantitative analytical study. Data collection was conducted by distributing questionnaires to 146 respondents. Data were analyzed using the Chi-Square test. The results showed that 69% of respondents were non-compliant with their medication regimen, while 31% were compliant. Regarding quality of life, 20% of respondents reported no problems, 22% reported mild problems, 24% moderate, 19% severe, and 15% very severe. In conclusion, there is a significant correlation between the level of compliance to antihypertensive medication use and the quality of life of elderly hypertensive patients at the Kresnomulyo Public Health Center, Pringsewu, with a significance level of 0.000 (p < 0.05).